Assessing the clinical accuracy of a hand hygiene system: learnings from a validation study - Hansen, Marco Bo; Wismath, Nina; Fritz, Evelyn Elisabeth; Heininger, Alexandra (American journal of infection control, 2021)
There is a need to establish validation standards that allow for comparison of automated hand hygiene systems. To assess the accuracy of an innovative monitoring tool (Sani nudge), 2 test nurses performed clinical standard tasks while being observed by 2 infection preventionists. Data from the direct observations were compared with data obtained from the hand hygiene system (Sani nudge) using an independent-event approach. We identified 54 true-positive events (100% system accuracy) and 4 true-negative events (100% system accuracy). No false-positive or false-negative events were identified. We found this approach to be feasible and clinically useful to validate hand hygiene systems in the future.